Ranking of countries in terms of the level of legal protection of human life at the prenatal stage of development - Bernaciak, Nikodem; Czelejczyk, Aniela; Olszówka, Marcin (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
Annex 1 presents a ranking of 196 countries by the level of legal protection of prenatal human life, based solely on comparing legal status, not enforcement practice, social attitudes, or actual abortion numbers. Countries are grouped into ten categories, from full protection of mother's and child's life to abortion on request, according to which grounds for terminating a pregnancy their laws permit (criminal-act, eugenic, maternal-health, or social/economic premises, alone or combined). Within categories, additional criteria apply: constitutional guarantees, severity of punishment, gestational age limits, and the mother's immunity. For federal states (the US, Australia) an average permissibility period was used; Mexico was assessed in light of Supreme Court rulings striking down state-level protections. A country-by-country table with sources and legal citations follows.